Russia and Islam : State, Society and Radicalism. - Dannreuther, Roland (BASEES/Routledge Series on Russian and East European Studies, 2010)
Examines contemporary developments in Russian politics, how they impact on Russia's Muslim communities, how these communities are helping to shape the Russian state, and what insights this provides to the nature and identity of the Russian state both in its inward and outward projection.